A Case of Follicular Atresia Triad Combined with Necrotising Fasciitis and Squamous Carcinoma of the Lower Limbs - Ai J; Sun Y; Yan M; Liu M; Zhong D; He W; Kang X; Chen X (Dove Medical Press, 2024)
Jinfeng Ai,1 Yihan Sun,2 Minrong Yan,1 Maolin Liu,1 Dongjun Zhong,1 Wei He,2 Xu Kang,2 Xinsheng Chen2 1The Second Clinical Medical College, Guangzhou University of Traditional Chinese Medicine, Guangzhou, People's Republic of China; 2Dermatology, Guangdong Provincial Hospital of Traditional Chinese Medicine, Guangzhou, People's Republic of ChinaCorrespondence: Xu Kang; Xinsheng Chen, Email Kangxuwf@163.com; xinshengchen@souhu.comAbstract: Follicular atresia triad, also known as paradoxical acne (FOT), is a rare and serious clinical syndrome in dermatology, mainly manifested by coalescing acne, purulent perifolliculitis of the head, and suppurative sweating inflammation, and FOT combined with necrotising fasciitis of the lower limbs and squamous cell carcinoma is rare both at home and abroad. In this article, we share the clinical data and treatment of a patient with follicular atresia triad and necrotising fasciitis and squamous cell carcinoma of the left lower limb for your reference.Keywords: follicular atresia triad, necrotising fasciitis, squamous cell carcinoma